Mind as a Behavioral Inhibition Network - Moriyama, Toru; Sonoda, Kohei; Saito, Hanna; Migita, Masao (Frontiers in Psychology, 2020)
This study aimed to propose to add a new perspective on what may create the impression of “mind" in other beings. The conventional perspective is that when we observe mental activities in animals, this creates in us the impression that they have a mind. On the other hand, the authors’ proposal is that when we observe unpredictable activities in living beings, this creates in us the impression of mind. This “unpredictability” is a characteristic product of all living things and is not limited to animals. In response to this additional perspective of mind, we assumed that the following questions would arise, “Is mind as the source of unpredictability an imaginary thing? Does it really exist?” To answer this question, a conceptual model of mind was proposed, and its validity was investigated by introducing studies on the relationship between animals’ unpredictability and emergent behavior. In section 1, we examined the question from the perspectives of comparative psychology, ethology, and neurophysiology. As a result, we obtained the hypothesis that every animal can have a “behavioral inhibition network” and that this corresponds with the source of unpredictability. The function of the behavioral inhibition network is to create “unpredictable behavior.” It makes an observer facing the animal feel unpredictability of the animal. However, unpredictable behavior may arise from exogenous factors such as congenital malfunction in the mechanism to generate an innately acquired behavior, as well as environmental disturbances. Therefore, in the second section, we introduce studies where unpredictable behavior seems to occur endogenously. In these studies, various animal species were examined in unexperienced problem-solving tasks that could not be solved by innately acquired behaviors. As a result, each animal solved the problem by generating unpredictable behaviors with high frequency. Such biologically significant unpredictable behaviors are referred to as “emergent behaviors”. In the discussion, we investigate whether the behavioral inhibition network matches the mind that one experiences in their daily life. Finally, toward a science of universal mind, we introduce experimental results suggesting the possibility that plants and materials such as stones have a similar structure to a behavioral inhibition network.